PENGARUH PENGALAMAN MEREK, KEPERCAYAAN, DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN TELEKOMUNIKASI GSM DI BATAM - Saputra, Suyono; Natalia, Via Marselina (2021)
Today's competition in the telecommunications industry demands service providers not only offer quality products but also memorable experiences for customers. The concept of brand experience is starting to become the focus of marketing practitioners in increasing customer loyalty. This study was conducted on 300 respondents who were registered as subscribers of GSM telecommunications services to explore the relationship between brand experience, trust, satisfaction, and loyalty. This study produces interesting findings that apart from emphasizing the significant relationship between the variables of brand experience, trust, customer satisfaction and loyalty, it also proves that the relationship between trust and loyalty, as well as brand experience on loyalty through trust as mediation, has no significant effect either directly or indirectly. live. In an effort to build customer loyalty, THE GSM company must be able to improve brand experience, trust and customer satisfaction. This brand experience can be understood as a way of sorting out services, to change customer perceptions of a brand, and ultimately be able to retain customers in the long term.